(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2022)
The aim of the research was to demonstrate the positive impact of sea on Poles and their recreational opportunities. As part of this aim, a questionnaire survey was conducted. The study took place at the turn of December and January 2020/2021. The questions included the respondents’ opinion on sea and its advantages. The survey questionnaire was created thanks to the Google Forms platform. The link assigned to it was made available on a nationwide group of walruses, on a social networking site such as Facebook. 411 respondents completed the questionnaire via the Internet. Thanks to the conducted research, it has been shown that sea water has a positive effect not only on the physical aspects of people who take cold baths, but also improves well-being and fulfills socialization needs.